O-137 Salpingectomy versus neosalpingostomy in women with hydrosalpinx: a prospective cohort study with long-term follow-up. (6th August 2021) - Yan, L; Zhu, C; Liang, G; He, C; Liang, Y; Zhao, X; He, X; Zhang, Y; Mol, B W; Huirne, J A F; Zhang, J
Abstract: Study question: What is the comparative effectiveness between salpingectomy and neosalpingostomy in the treatment of bilateral severe hydrosalpinx? Summary answer: In women with bilateral severe hydrosalpinx, salpingectomy combined with In Vitro Fertilization (IVF) treatment resulted in a higher cumulative live birth rate than neosalpingostomy. What is known already: Hydrosalpinx accounts for 25% to 35% of female subfertility and has a negative effect on pregnancy rates in women who undergo IVF. So far salpingectomy before in vitro fertilization treatment has been suggested for the treatment of hydrosalpinx in order to improve the chance of a live birth. Previous studies have reported a pooled live birth rate of 25% through natural conception after neosalpingostomy and an ongoing pregnancy rate of 55.8% after salpingectomy with IVF. Direct comparison of the cumulative live birth rate after salpingectomy versus neosalpingostomy, both followed by IVF is lacking. Study design, size, duration: We performed a single center, prospective comparative cohort study in the International Peace Maternity and Child Health Hospital affiliated to Shanghai Jiao Tong University School of Medicine, China. We studied women diagnosed with tubal subfertility with bilateral hydrosalpinx between January 2005 and December 2012. Based on a shared decision approach, they had bilateral salpingectomy or neosalpingostomy followed by IVF. They were annually followed up until July 2020 for the occurrence of live birth. Participants/materials, setting, methods: Out of 113 women, 55 had bilateral salpingectomy and 58 had bilateral neosalpingostomy. Primary outcome was cumulative live birth rate, defined as the cumulative birth rate of the first living neonate through either natural conception or in vitro fertilization. Both intention-to-treat (ITT) and per-protocol (PP) analysis were processed. Cox proportional hazards regression model with potential variables was performed to identify predictors of successful live birth. Main results and the role of chance: Baseline characteristics were comparable between two groups. There were 42 live births in the salpingectomy and 36 in the neosalpingostomy group. When the result of IVF was incorporated (55/55 in salpingectomy group and 25/58 in neosalpingostomy group underwent IVF), salpingectomy resulted in a higher cumulative live birth rate (85.3% vs 76.0%; hazard ratio of the whole survival curve, 2.18; 95% CI, 1.37 - 3.45; P = 0.001), a lower risk of ectopic pregnancy (1.8% vs 20.7%; risk ratio, 0.07; 95% CI, 0.01 - 0.57; P = 0.013), and a shorter time to live birth (19 [14, 27] versus 36 [17, 76] months, P = 0.001).The number of live birth rates after natural conception was 0% (0/55) in the salpingectomy group and 28% (16/58) in neosalpingostomy group.The results of PP analyses were comparable with the ITT analyses apart from the biochemical pregnancy rate and the overall live birth rate, they were higher (the former: 76% (42/55) versus 58% (29/50), P = 0.045; the latter: 76% (42/55) versus 56% (28/50), P = 0.027) in salpingectomy group. Limitations, reasons for caution: This is an observational study. The small sample size along with the data was obtained from a cohort study in a single center. Wider implications of the findings: In women with confirmed bilateral severe hydrosalpinx, salpingectomy followed by IVF results in a higher cumulative live birth rate and decreases the risk of EP as compared to neosalpingostomy. However, neosalpingostomy is the only option to achieve a live birth by natural conception that should be discussed with patients preoperatively. Trial registration number: not applicable